Immunogenicity of Protein Therapeutics: A Lymph Node Perspective - Fu, Kristy; March, Kylie; Alexaki, Aikaterini; Fabozzi, Giulia; Moysi, Eirini; Petrovas, Constantinos (Frontiers in Immunology, 2020)
The continuous development of molecular biology and protein engineering technologies enables the expansion of the breadth and complexity of protein therapeutics for in vivo administration. However, the immunogenicity and associated in vivo development of antibodies against therapeutics is a major restriction factor for their usage. The B cell follicular and particularly germinal center areas in secondary lymphoid organs are the anatomical sites where the development of antibody responses against pathogens and immunogens takes place. A growing body of data has revealed the importance of the orchestrated function of highly differentiated adaptive immunity cells, including follicular helper CD4 T cells and germinal center B cells, for the optimal generation of these antibody responses. Understanding the cellular and molecular mechanisms mediating the antibody responses against therapeutics could lead to novel strategies to reduce their immunogenicity and increase their efficacy.